Infrastructure and Growth in Developing Countries : Recent Advances and Research Challenges - Straub, Stéphane (World Bank, Washington, DC, 2012)
This paper presents a survey of recent research on the economics of infrastructure in developing countries. Energy, transport, telecommunications, water and sanitation are considered. The survey covers two main set of issues: the linkages between infrastructure and economic growth (at the economy-wide, regional and sectoral level) and the composition, sequencing and efficiency of alternative infrastructure investments, including the arbitrage between new investments and maintenance expenditures; OPEX and CAPEX, and public versus private investment. Following the introduction, section 2 discusses the theoretical foundations (growth theory and new economic geography). Section 3 assesses the analysis of 140 specifications from 64 recent empirical papers-examining type of data used, level of aggregation, econometric techniques and nature of the sample-and discusses both the macro-econometric and micro-econometric contributions of these papers. Finally section 4 discusses directions for future research and suggests priorities in data development.